Parameter- und Ordnungsidentifikation von fraktionalen Systemen mit einer Anwendung auf eine Lithium-Ionen-Batteriezelle - Stark, Oliver (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
Model-based methods are increasingly being used for a safe and efficient operation of battery cells. For modeling battery cells, fractional models which are characterized by non-integer derivative orders have become established due to their electrochemical interpretability. In this work, methods for parameter and derivative order identification of fractional systems are derived without restriction with respect to the excitation at the begin of identification.